Penerapan Model Index Card Match untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam pada Siswa Sekolah Dasar - Nurainah Nurainah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Learning Islamic Religious Education (PAI) in elementary schools should ideally be interactive and engaging, fostering a deep understanding of concepts and the internalization of religious values. Objective: This study aims to implement and analyze the effectiveness of the Index Card Match learning model in enhancing student engagement and learning outcomes for fourth-grade students on the topic of Asmaul Husna at SDN 02 XIV Koto. Method: The research used Classroom Action Research (CAR) in two cycles, with data collected through observation, interviews, learning outcome tests, and documentation. A mixed-methods approach was applied, combining qualitative descriptive analysis to describe learning activities and quantitative analysis to measure improvements in student achievement. Result: The findings indicate a significant improvement from the pre-cycle to Cycle II, with mastery learning increasing from 25% to 80%. There was also consistent growth in student participation and motivation during each meeting. Conclusion: The Index Card Match model is effective in enhancing student engagement, conceptual understanding, and PAI learning outcomes, particularly in the Asmaul Husna topic. The model promotes active participation, allowing students to interact with the material in a more meaningful and enjoyable way. Contribution: This study contributes to strengthening empirical evidence regarding the effectiveness of game-based cooperative learning models in PAI and provides practical recommendations for teachers on how to implement active learning strategies that align with the developmental characteristics of elementary school students.